IN VITRO ANTIPLATELET AND ANTICOAGULANT ACTIVITY OF INDIGENOUS VEGETABLES FROM SOUTHERN THAILAND - SUKATI, SURIYAN; KHOBJAI, WARACHATE (International Journal of Applied Pharmaceutics, 2021)
Objective: Epidemiological studies have indicated that diets rich in fruits and vegetables help reduce the risk of cardiovascular diseases (CVDs). However, data about the antithrombotic activity of local vegetables is rare. The objective of this study was to evaluate antiplatelet and anticoagulant activity in indigenous vegetables with high phenolic compounds collected from Southern Thailand. Methods: Five selected indigenous vegetables were crudely extracted by distilled water and 80% methanol. The extracts were screened for in vitro antiplatelet and anticoagulant activity at a concentration of 10 μg/μl. The antiplatelet activity was measured by inhibition of platelet adhesion to collagen and thrombin-induced platelet aggregation, while the anticoagulant activity was assessed by the prothrombin time (PT) and activated partial thromboplastin time (APTT) tests. Results: Among the selected vegetables, the extracts of mon-pu (Glochidion perakense Hook.f.) and young cashew leaves (Anacardium occidentale L.) showed high antithrombotic properties. The highest antithrombotic activity was observed in the methanolic extract of mon-pu, which showed 92.79±0.78% of platelet adhesion inhibition, 102.9±1.53% of platelet aggregation inhibition, and a prolonged APTT assay (48.92±0.94 s). The prolonged APTT but normal PT results suggested that the extract could affect factors VIII, IX, XI, and XII of the intrinsic coagulation pathway. Conclusion: Our findings demonstrated antiplatelet and anticoagulation properties of indigenous vegetables from Southern Thailand. The multipotential effects of mon-pu extracts on antithrombosis evidently suggest that mon-pu can be considered as an excellent nutraceutical option in the prevention of thrombosis-related CVDs caused by different mechanisms.